Composting as One of Modern Methods for Utilizing Meat Processing Waste - Farzona, Narzieva; Farziniso, Narzieva (American Journal of Biodiversity, 2025)
The meat processing industry generates large quantities of organic waste that pose environmental and sanitary challenges if not properly managed. Traditional disposal methods, such as landfilling and incineration, contribute to greenhouse gas emissions and soil contamination. Composting has emerged as an environmentally sustainable, cost-effective, and biologically efficient method for utilizing meat processing by-products. This paper explores the principles, processes, and advantages of composting as a method for managing meat processing waste, supported by recent research findings. It also evaluates the efficiency of composting in nutrient recovery, pathogen reduction, and its potential for circular economy applications in agriculture.